Anaesthetic Management of a Patient with Subarachnoid Hemorrhage, Multiple Cerebral Aneurysms and Type IV Takayasu Arteritis - Agrawal, Sanket; Gupta, Shailesh; Bhagat, Hemant; Gandhi, Komal; Singla, Navneet (Journal of Neuroanaesthesiology and Critical Care, 2018)
Takayasu's arteritis (TA), also known as pulseless disease, is a granulomatous panarteritis affecting large vessels, predominantly the aorta and its main branches. Twenty percent of TA cases present with central nervous system involvement. It typically manifests as cerebral ischemia or stroke, when central nervous system disease is present. There are rare reports of intracranial aneurysms in adults with TA. We report the anesthetic management of a 16-year old female patient with TA type IV with multiple cerebral aneurysm with subarachnoid hemorrhage.
Keywords: cerebral aneurysm; hypertension; Takayasu arteritis